Gambaran Adult Attachment Style Pada Istri yang Menjalani Long Distance Marriage (LDM) - Ria Aprillia; Eska Prawisudawati Ulpa (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to describe adult attachment styles among wives who experience long distance marriage (LDM) with husbands working as migrant workers. This research employed a qualitative method with a phenomenological approach. Participants were selected purposively, consisting of married women who had experienced LDM for at least three months and were in early to middle adulthood. Data were collected through in-depth interviews. The findings indicate that secure attachment is the most dominant attachment style among participants. However, anxious attachment emerged situationally in response to communication barriers, physical distance, and relational uncertainty, while avoidant attachment appeared in the lowest proportion. These results suggest that wives in long distance marriages generally possess a relatively secure attachment foundation and demonstrate emotional adaptability in maintaining marital relationships despite physical separation.